Phenolic content and antioxidant action in needle extracts from Pinus cooperi, P. durangensis, P. engelmanii and P. teocote - Sáenz-Esqueda, María de los Ángeles; Rosales-Castro, Martha; Rocha-Guzmán, Nuria Elizabeth; Gallegos-Infante, José Alberto; González-Laredo, Rubén Francisco (Instituto de Ecología, A.C., 2016)
Coniferous trees are a vast resource in Durango, Mexico forests and a potential nontimber source of these chemicals, thus, our study for analyzing phenolic content and biological activity in needle extracts from Pinus cooperi (COO), P. durangensis (DUR), P. engelmanii (ENG) and P. teocote ( TEO). Pine needles were dewaxed with hexane and extracted with aqueous acetone and methanol. DUR and ENG extracts showed the higher yields, while acetone TEO and methanol ENG extracts showed the highest catechin equivalent (CE) contents. A partial chromatographic purification on acetone TEO extracts produced five fractions, the third one (F3-TEO) had the highest phenolic content (489,6 CE). In condensed tannins contents, acetone and methanol TEO extracts, as well fraction F3-TEO were the best (24,3, 15.7 and 44,4 mg/g extract, respectively). In DPPH activity, the more effective CE50 were obtained from TEO acetone extract (223,5 ppm) and fractions F3-TEO (145,0 ppm) and F4-TEO (150,8 ppm). In ABTS assay, TEO acetone (27,7%) and methanolic (18,2%) extracts, and fractions F3-TEO (60,1%) and F4-TEO (55,8%) were the best. In LDL assay the highest inhibitory activity was shown by acetone extracts, particularly ENG (99,4%) at 90 ppm. Therefore acetone extracts from TEO and ENG may have utilization as a potential source of bioactive phenolics.